Digital Gaming for Improving the Functioning of People With Traumatic Brain Injury: Protocol of a Feasibility Study - Välimäki M; Korkeila J; Kauppi K; Kaakinen JK; Holm S; Vahlo J; Tenovuo O; Hämäläinen H; Sarajuuri J; Rantanen P; Orenius T; Koponen A (JMIR PUBLICATIONS, 2025)
The specific outcomes such as primary outcome measures were selected because they are widely used psychological tests and thought to be sensitive to changes in the cognitive functions related to TBI.